Analisis Kepemimpinan Kepala Sekolah dalam Menerapkan Budaya Sekolah Positif di SD Negeri Gedangan, Welahan, Jepara - Solfia Mujiarti; Ahmad Hariyadi; Erik Aditya Ismaya (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study aims to determine teachers’ perceptions of the principal’s leadership style, describe the principal’s leadership style in managing schools, describe the principal’s role in implementing a positive school culture at Gedangan Elementary School, and analyze the relationship between the principal’s leadership style and the level of positive culture implementation perceived by teachers at Gedangan Elementary School. This study uses a mixed methods approach with a sequential explanatory design. The initial phase involved collecting quantitative data through open-ended questionnaires, which were analyzed descriptively using thematic coding. The next phase involved collecting qualitative data through interviews with the principal, teachers, and students, as well as school documentation, which was analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results of the study indicate that 1) teachers perceive the principal as a sincere, honest, communicative, and motivating person, contributing to a safe and comfortable work environment; 2) the principal’s leadership style at Gedangan Elementary School is democratic and participatory, involving teachers in planning, decision-making, and implementing school programs, thus creating a harmonious and collaborative work climate; 3) the principal’s role in implementing a positive culture is realized through role modeling, participatory decision-making, and a sustainable school culture program that aims to instill the values ​​of discipline, responsibility, and mutual respect; and 4) a participatory and communicative leadership style is closely related to the implementation of a strong positive school culture, which is demonstrated by harmonious collaboration, a culture of appreciation, and a conducive school atmosphere.This study aims to determine teachers’ perceptions of the principal’s leadership style, describe the principal’s leadership style in managing schools, describe the principal’s role in implementing a positive school culture at Gedangan Elementary School, and analyze the relationship between the principal’s leadership style and the level of positive culture implementation perceived by teachers at Gedangan Elementary School. This study uses a mixed methods approach with a sequential explanatory design. The initial phase involved collecting quantitative data through open-ended questionnaires, which were analyzed descriptively using thematic coding. The next phase involved collecting qualitative data through interviews with the principal, teachers, and students, as well as school documentation, which was analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results of the study indicate that 1) teachers perceive the principal as a sincere, honest, communicative, and motivating person, contributing to a safe and comfortable work environment; 2) the principal’s leadership style at Gedangan Elementary School is democratic and participatory, involving teachers in planning, decision-making, and implementing school programs, thus creating a harmonious and collaborative work climate; 3) the principal’s role in implementing a positive culture is realized through role modeling, participatory decision-making, and a sustainable school culture program that aims to instill the values ​​of discipline, responsibility, and mutual respect; and 4) a participatory and communicative leadership style is closely related to the implementation of a strong positive school culture, which is demonstrated by harmonious collaboration, a culture of appreciation, and a conducive school atmosphere.